Pharmacological suppression of seizure‐like activity in the PS2APP model of amyloidosis: Development of new models and analysis methods/amyloid/Abeta. (7th December 2020) - Weber, Martin; Imperio, Jose; Gandham, Vineela; Meilandt, William; Hanson, Jesse E.; Easton, Amy E.; Elstrott, Justin
Abstract: Background: Seizure activity is significantly increased in patients with Alzheimer Disease relative to healthy controls. Concurrently, the J20 mouse model of amyloidosis has increased seizure‐like activity, and compounds that lower this activity can lead to cognitive benefits in this model. Here we aim to extend these studies to the PS2APP mouse model of amyloidosis. Method: Locomotor activity was measured for 60 min in C57BL/6J mice with a beam‐break based monitoring system (PAS Open Field, San Diego Instruments) using a between‐subjects design with 9‐10 mice/dose group. EEG/EMG headmounts were implanted into PS2APP mice with amyloid‐beta pathology. Data was recorded for 6h using a Pinnacle Technologies recording system and processed with MATLAB (Mathworks) routines. EEG spikes were detected using a thresholded line‐length algorithm.A within subject crossover‐design was used for vehicle vs. Levetiracetam treatment and data from 13 PS2APP mice was analyzed. Result: Locomotor activity measures showed that an acute dose of 200 mg/kg of the anti‐seizure medication Levetiracetam did not affect activity levels. EEG recordings demonstrated that the frequency of seizure‐like spikes during sleep was increased from 38 spikes/h in 4 months old PS2APP mice to 75 spikes/h in 13 months old PS2APP mice. This measure was reduced by ∼60% in 13 months old PS2APP mice in response to acute treatment with 200 mg/kg of Levetiracetam. Conclusion: Seizure‐like activity is increased in patients with Alzheimer's disease and in mouse models of amyloidosis. Our Levetiracetam studies confirm that pharmacological intervention can normalize seizure‐like activity in PS2APP mice. Medications with different mechanism of action need to be tested for their ability to reduce spike activity and improve cognition in this animal model.Ultimately, it will be important to see if such pharmacological effects translate to humans and if reductions in seizure activity are linked to functional improvements.